COMMUNITY EMPOWERMENT IN STUNTING PREVENTION EFFORTS THROUGH AN EDUCATION PROGRAM AT POSYANDU NUSA INDAH TUJUH - Purnamawati, Nike; Muzdalifah, Safa; Qubayla, Farah; Rahman Hakim, Arif; Kristanto, Budi; Hamidah, Siti; Fatori, Ach.; Bhakti Mafriana, Sandra (Sivitas : Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2026)
This community service program aims to empower pregnant women and mothers with infants and toddlers through a stunting education program. This was carried out to increase public knowledge and awareness about stunting prevention, especially for the community at the Nusa Indah Tujuh Integrated Health Post (Posyandu), Handil Bakti Village. This community service activity was attended by 35 participants and was carried out in three stages: community empowerment education regarding stunting and a pre-test, in-depth counseling on the definition and prevention of stunting in collaboration with the Semangat Dalam Community Health Center, and activity evaluation focused on the implementation of a post-test. The counseling material covered the definition, causes, impacts and methods of preventing stunting including the importance of balanced nutrition, exclusive breastfeeding, and the use of local foods. The pre-test results showed that more than 50% of participants did not know how to prevent stunting, the long-term impacts, and the vulnerable age of stunting due to the participants having never received counseling about stunting before. The post-test results showed a significant increase in understanding, where 100% of participants stated that they knew what stunting is and how to prevent it. This program has successfully empowered communities by increasing knowledge and awareness, which encourages behavioral changes towards a healthy lifestyle to prevent stunting independently and sustainably